Microbiological quality of raw edible vegetables sampled from cafeterias at Universiti Sains Malaysia, Kubang Kerian, Kelantan - Dianne, Kua Vee May (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2013)
Raw fruits and vegetables have been known to serve as vehicles of human diseases and food borne outbreaks have increased in recent years. Raw vegetables contaminated with pathogenic bacteria may lead to health hazard as there is no treatment that can be relied upon for decontamination of the vegetables. A study was conducted to screen and identify the bacterial pathogens present in selected raw vegetables sold in the cafeterias in USM Health Campus. A total of 30 samples from six commonly consumed raw vegetables viz., cucumber, winged bean, lettuce, wild cosmos, pennywort leaves and water dropwort were analyzed. Samples were randomly collected over a period of two months. Fifty grams (50g) from each sample were taken for microbiological analysis. The presence and identification of pathogenic bacteria viz., E.coli, Bacillus cereus, Staphylococcus aureus, Salmonella and total coliforms was determined based on the "Australian Microbiological Examination of Food", (1993) and the analysis was conducted in triplicates. Compliance to the microbiological quality (CFU/g) of raw vegetables is based on the "Microbiology Guidelines for Ready to Eat Food" MOH Malaysia ( 1985). The results showed that the total coliforms were presence in all vegetables samples (~1,000 CFU/g, unsatisfactory). A total of 6 (20%) samples (1 cucumber, 1 pennywort, 3 water dropwort and 1 wild cosmos) showed presence of pathogenic bacteria namely E.coli and Salmonella. However, lettuce and winged bean did not show presence of any of the pathogenic bacteria. E. coli was detected ( 3-1 00 CFU/g , marginal) in 25% of the pennywort, 22.2% water dropwort (3x 103 -5x 1 oJ CFU/g, unsatisfactory), and 50% wild cosmos samples (1x103 CFU/g, unsatisfactory). Meanwhile, Salmonella was detected in 12.5% of the cucumber and 11.1% water dropwort samples. However, the presence of Bacillus cereus and Staphylococcus aureus were not detected in any of the raw vegetables sampled. Our findings revealed that all vegetables samples showed presence of total coliforms, and some with E.coli and Salmonella, exceeding the safe level described by "Microbiology Guidelines for Ready to Eat Food" MOH Malaysia (1985), and this can be construed that the contaminated vegetables may pose considerable hazards on human health. Furthermore, further identification has led to the detection of an enteric serovar weltevreden which has been implicated with several cases of food borne illnesses (Bangtrakulnonth, 2004). However, no pathogenic E.coli was isolated in this study. Thus, further study should be carried out to determine the source of contamination so that measures can be taken to improve the microbiological quality of raw vegetables sold in Health Campus, USM.